Managerial Ownership, Financial Performance and Firm Value: Evidence from Consumers Goods Company Listed in Indonesia Stock Exchange - Harnida, Muthia; Rizka Zulfikar; Siti Mardah; Dian Titania Rahman (International Journal of Science, Technology & Management, 2021)
The research about the impact of financial performance on firm value has become great attention to financial issues in various researches. Financial performance provides information needed by investors. Firm value is used to reflect the real value of the company more realistically by considering the concept of market value. The investors need the actual value of the firm to be a factor to consider for them to invest. This research is aimed at examining the impact of the financial performance of profitability, liquidity, leverage, and activity ratio. We also examine if there were managerial ownership effects the relationship among those financial performances on the firm value using the proxy of Tobin's Q. The sample used is the Consumers Goods Companies which listed in the Indonesia Stock Exchange for the period from 2015 to 2019. We used purposive sampling for obtaining 70 observations. We analyzed data using multiple linier regression, and moderated- regression analysis. The study indicates that profitability and leverage statistically affect the firm value. But, the liquidity and activity ratio with the proxy of total asset turnover has no significant impact on firm value. Other result were the moderation has significant effect of managerial ownership strengthens the relationship of debt to equity ratio and total assets turnover.